ASEAN on Malaysia on 31st August 2001: a study of online newspapers - Fuziah Kartini Hassan Basri,; Arfah Yusof,; Mohd Safar Hasim,; Normah Mustafa, (Universiti Kebangsaan Malaysian, 2002)
please refer fulltext